O impacto da exposição a experiências adversas na infância na ocorrência de dor crônica e depressão na vida adulta - Pereira, Flavia Garcia (2014)
Association between adverse childhood experiences and onset- depression or chronic pain in adulthood has been documented, as well as the relationship between symptoms of comorbidity chronic pain and depression. However, the literature is extremely limited about the interaction of adverse childhood experiences in this comorbidity. The objective of this study is to evaluate the influence of adverse childhood experiences in depression, chronic pain and on the comorbidity of chronic pain and depression in adulthood in a probabilistic sample of household adult residents in the Sao Paulo Metropolitan Area, Brazil. The data were resulting from the São Paulo Megacity Mental Health Survey. Respondents were assessed using the World Mental Health Survey version of the World Health Organization Composite International Diagnostic Interview (WMH-CIDI), which comprises clinical and no-clinical sections producing diagnoses according to the Diagnostic and Statistical Manual of Mental Disorders – Fourth Edition (DSM-IV). A total of 5,037 individuals were interviewed, with a global response rate of 81.3%. Descriptive analysis for means and proportions were performed, and associations between adverse childhood experiences, chronic pain and depression were performed using logistic regression with statistical software Data Analysis and Statistical Software version 12.0 (STATA 12.0), using 0.05 level two-sided tests. High prevalence of chronic pain (31%, standard error [ER] = 0.8) was found. Chronic pain was associated to anxiety disorders (OR 2.3, 95% CI 1.9-3.0), mood disorders (OR 3.3; 95% CI 2.6-4.4) in any mental disorder (OR 2.7; 95% CI 2.3-3.3). The childhood adversities were strongly associated with comorbidity chronic pain and depression, especially physical abuse (OR 2.7, 95% CI 2.1-3.5) and sexual abuse (OR 7.4, 95% CI 3.4-16.1).